The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1096/fj.05-4759com
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐catenin regulates wound size and mediates the effect of TGF‐beta in cutaneous healing

Abstract: After cutaneous injury, a variety of cell types are activated to reconstitute the epithelial and dermal components of the skin. beta-Catenin plays disparate roles in keratinocytes and fibroblasts, inhibiting keratinocyte migration and activating fibroblast proliferation, suggesting that beta-catenin could either inhibit or enhance the healing process. How beta-catenin functions in concert with other signaling pathways important in the healing process is unknown. Wound size was examined in mice expressing condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
201
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(212 citation statements)
references
References 47 publications
(55 reference statements)
8
201
1
Order By: Relevance
“…Previous studies have used only the width of the fibrotic area as a measure of scar size and did not delineate the entire scar area. 29,30 By dividing the scar area by the corresponding average scar thickness, our methodology not only measures the entire scar area but is also able to account for variability in skin thickness. Using this approach, we demonstrated that in addition to anatomic regional differences, various other factors such as age, sex, and scar age could influence dermal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used only the width of the fibrotic area as a measure of scar size and did not delineate the entire scar area. 29,30 By dividing the scar area by the corresponding average scar thickness, our methodology not only measures the entire scar area but is also able to account for variability in skin thickness. Using this approach, we demonstrated that in addition to anatomic regional differences, various other factors such as age, sex, and scar age could influence dermal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…NaCl or LiCl was added to the drinking water to a final concentration of 0.014 M. This dosage was previously shown to elevate ␤-catenin in mesenchymal cells in mice (6,36). An adenovirus that expresses DKK-1 (32), CRE-recombinase, or GFP as a control (6), was administered to wild type or genetically modified mice 4 days prior to wounding.…”
Section: Treatment Of Mice With Lithiummentioning
confidence: 99%
“…NaCl or LiCl was added to the drinking water to a final concentration of 0.014 M. This dosage was previously shown to elevate ␤-catenin in mesenchymal cells in mice (6,36). An adenovirus that expresses DKK-1 (32), CRE-recombinase, or GFP as a control (6), was administered to wild type or genetically modified mice 4 days prior to wounding. The mice were injected subcutaneously with the adenovirus at a titer of 1 ϫ 10 8 plaque-forming units at the future wound site, and also intraperitoneally, as previously reported (6,37,38); Eda Fn Ϫ/Ϫ ; Catnb tm1Tak mice were injected with a dose of 5 ϫ 10 7 plaqueforming units/site of an adenovirus driving expression of CRErecombinase, or GFP, as previously reported (6).…”
Section: Treatment Of Mice With Lithiummentioning
confidence: 99%
See 2 more Smart Citations